Molecular Imprints Frozen by Strong Intermolecular Interactions in Place of Cross‐Linking. Issue 6 (29th December 2020) - Ayadi, Cherifa; Anene, Amira; Kalfat, Rafik; Chevalier, Yves; Hbaieb, Souhaira
Abstract: A new way to freeze molecular imprints in a polymer material is reported. So far, molecular imprinted polymers (MIP) involve copolymerization of a functional monomer and large amounts of cross‐linking agent, which keeps the template shape memory in rigid molecular imprints. MIP materials are prepared herein without cross‐linking agent. Stiff chains of polyaniline grafted on a solid support as a brush‐like material achieve the necessary rigidity. Differential adsorption to imprinted and non‐imprinted materials provides evidence of molecular imprints. A correct adsorption isotherm for mobile adsorbed layers (Volmer isotherm) is introduced instead of the popular but inadequate Langmuir isotherm. Non‐selective adsorption is entropic, whereas adsorption to molecular imprints has an enthalpic contribution coming from specific interactions. Fast adsorption kinetics are a definite benefit with regards to applications such as chromatographic separations and chemical sensors. Abstract : Frozen imprints : A new way to freeze molecular imprints in a polymer material is reported. Usually, molecular imprinted polymers (MIP) involve copolymerization of a functional monomer and large amounts of cross‐linking agent. Here, MIPs are prepared without cross‐linking agent by using stiff chains of polyaniline grafted on a solid support, and their adsorption kinetics are studied.